Molecular phylogeny of Asian Meconopsis based on nuclear ribosomal and chloroplast DNA sequence data. - Yu-Cheng Liu; Ya-Nan Liu; Fu-Sheng Yang; Xiao-Quan Wang (PLoS ONE, 2014)
The taxonomy and phylogeny of Asian Meconopsis (Himalayan blue poppy) remain largely unresolved. We used the internal transcribed spacer (ITS) region of nuclear ribosomal DNA (nrDNA) and the chloroplast DNA (cpDNA) trnL-F region for phylogenetic reconstruction of Meconopsis and its close relatives Papaver, Roemeria, and Stylomecon. We identified five main clades, which were well-supported in the gene trees reconstructed with the nrDNA ITS and cpDNA trnL-F sequences. We found that 41 species of Asian Meconopsis did not constitute a monophyletic clade, but formed two solid clades (I and V) separated in the phylogenetic tree by three clades (II, III and IV) of Papaver and its allies. Clade V includes only four Asian Meconopsis species, with the remaining 90 percent of Asian species included in clade I. In this core Asian Meconopsis clade, five subclades (Ia-Ie) were recognized in the nrDNA ITS tree. Three species (Meconopsis discigera, M. pinnatifolia, and M. torquata) of subgenus Discogyne were imbedded in subclade Ia, indicating that the present definition of subgenera in Meconopsis should be rejected. These subclades are inconsistent with any series or sections of the present classifications, suggesting that classifications of the genus should be completely revised. Finally, proposals for further revision of the genus Meconopsis were put forward based on molecular, morphological, and biogeographical evidences.